Cardiovascular control, autonomic function, and elite endurance performance in spinal cord injury. Issue 4 (31st August 2014) - West, C. R.; Gee, C. M.; Voss, C.; Hubli, M.; Currie, K. D.; Schmid, J.; Krassioukov, A. V.
<x xml:space="preserve">Abstract</x> We aimed to determine the relationship between level of injury, completeness of injury, resting as well as exercise hemodynamics, and endurance performance in athletes with spinal cord injury (SCI). Twenty‐three elite male paracycling athletes (C3‐T8) were assessed for neurological level/completeness of injury, autonomic completeness of injury, resting cardiovascular function, and time to complete a 17.3‐km World Championship time‐trial test. A subset were also fitted with heart rate (HR) monitors and their cycles were fitted with a global positioning systems device (n = 15). Thoracic SCI exhibited higher seated systolic blood pressure along with superior time‐trial performance compared with cervical SCI (all P < 0.01). When further stratified by autonomic completeness of injury, the four athletes with cervical autonomic incomplete SCI exhibited a faster time‐trial time and a higher average speed compared with cervical autonomic complete SCI (all P < 0.042). Maximum and average HR also tended to be higher in cervical autonomic incomplete vs autonomic complete. There were no differences in time‐trial time, HR, or speed between thoracic autonomic complete vs incomplete SCI. In conclusion, autonomic completeness of injury and the consequent ability of the cardiovascular system to respond to exercise appear to be a critical determinant of endurance performance in elite athletes with cervical SCI.